Enhancing learners' English language proficiency through service learning : an investigation on BRAC University perspective - Rahman, Md. Mahbubur (BRAC University, 2013)
Service Learning concept shows the positive impacts on the active engagement of English language teachers as well as learners in creating appropriate scope for making a learning community both inside and outside the classroom. The students are perfectly connected to community service with the direct use of their integrated language skills unlike the traditional classroom teaching. Considering that fact, learners are put in real life situations to experience language skills so that instead of learning English, the learners have the scope for language acquisition. With a view to ensuring that principle, BRAC University has incorporated Starboard activity, English Week observance etc. as parts of integration between two academic courses: English and Ethics. This paper shows the impacts of these service-learning activities in improving the skills of language learners through investigating as well as carrying a message: “Serve to Learn”. After gathering data, SPSS copyright version 14 computer packages and Microsoft Office Excel 2007 version have been used to assess them.